Haptische, visuelle und olfaktorische Sprachen:Westnilotische Wahrnehmungen - Storch, Anne (AAeO - Afrikanistik-Aegyptologie-Online, 2005)
This article deals with the expression of sensual perceptions in Western Nilotic languages. The first part of the article presents ophresiological terminology in Lwoo and Burun languages, whereby it is demonstrated that words denoting smells can form a word class of its own in some of the languages. This world-wide rare phenomenon is still poorly understood and little described, so that the paper aims at giving a first insight into the topic. The second part of the article deals with the description of colours in Western Nilotic. Differentiated colour terminology is only found in connection with livestock vocabulary and as such largely depends on cultural patterns and socioeconomic patterns. The section aims at demonstrating that the parameters do change and colour terminology may also refer to other domains. The third part of the article presents an overview of the nominal classifiers in Mabaan (Burun), whereby a categorisation according to haptic principles is described as the underlying cognitive structure. As a result, different grammaticalisation paths are assumed and correlated with punctuations in the cultural and mental history of the speakers’ ancestors.